2011
DOI: 10.1161/hypertensionaha.110.167486
|View full text |Cite
|
Sign up to set email alerts
|

Selective Endothelin-A Receptor Antagonism Reduces Proteinuria, Blood Pressure, and Arterial Stiffness in Chronic Proteinuric Kidney Disease

Abstract: Abstract-Proteinuria is associated with adverse cardiovascular and renal outcomes that are not prevented by current treatments.Endothelin 1 promotes the development and progression of chronic kidney disease and associated cardiovascular disease. We, therefore, studied the effects of selective endothelin-A receptor antagonism in proteinuric chronic kidney disease patients, assessing proteinuria, blood pressure (BP), and arterial stiffness, key independent, surrogate markers of chronic kidney disease progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 41 publications
5
110
0
1
Order By: Relevance
“…21 In brief, in a randomized, double-blind, three-way crossover study, 27 patients receiving recommended renoprotective treatment underwent 6 weeks of placebo; sitaxentan, 100 mg once daily; and nifedipine long-acting, 30 mg once daily. Twenty-four-hour proteinuria, urine protein-to-creatinine ratio, 24-hour ambulatory BP, and PWV (as an index of arterial stiffness) were measured at baseline, week 3, and week 6 of each treatment period.…”
Section: Concise Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In brief, in a randomized, double-blind, three-way crossover study, 27 patients receiving recommended renoprotective treatment underwent 6 weeks of placebo; sitaxentan, 100 mg once daily; and nifedipine long-acting, 30 mg once daily. Twenty-four-hour proteinuria, urine protein-to-creatinine ratio, 24-hour ambulatory BP, and PWV (as an index of arterial stiffness) were measured at baseline, week 3, and week 6 of each treatment period.…”
Section: Concise Methodsmentioning
confidence: 99%
“…20 Its effects are mediated via two receptors, the ET A and ET B receptors; the major pathologic effects are ET A receptor mediated. 20 We have recently shown that long-term selective ET A receptor antagonist therapy using the orally active drug sitaxentan reduces proteinuria, BP, and arterial stiffness in patients with proteinuric CKD, 21 effects that are potentially renoprotective. We hypothesized that in this same cohort of patients with CKD, sitaxentan would also reduce levels of serum uric acid, ADMA, and urine ET-1 (as a measure of renal ET-1 production) and so provide broader cardiovascular and renal protection.…”
mentioning
confidence: 99%
“…Because of the natriuretic and antihypertensive properties of ET B receptors, blockade of ET B receptors in these studies may have counteracted any beneficial effects of ET A receptor blockade. More recently, sitaxsentan, a very specific ET A blocker, was shown to reduce blood pressure and proteinuria in patients with chronic kidney disease (5). Therefore, determining the importance of ET-1 in human essential hypertension deserves further investigation.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…8 Its effects are mediated via 2 receptors, the ET-A (ET A ) and ET-B (ET B ) receptors, with the major pathological effects being ET A receptor mediated. 8 We have shown recently that chronic selective ET A receptor antagonism reduces proteinuria, blood pressure, and arterial stiffness in patients with nondiabetic, hypertensive, proteinuric CKD, 9 effects that are potentially renoprotective. The current data show the effects of sitaxsentan and placebo on sUA in this same cohort of CKD patients.…”
Section: Chronic Selective Endothelin a Receptor Antagonism Reduces Smentioning
confidence: 99%
“…9 In brief, in a randomized, double-blind, 3-way crossover study, 27 subjects on recommended renoprotective treatment received 6 weeks of placebo, sitaxsentan 100 mg once daily and nifedipine LA 30 mg once daily. Twenty-four-hour proteinuria, urine protein:creatinine ratio, 24-hour ambulatory blood pressure, and pulse wave velocity, as an index of arterial stiffness, were measured at baseline, week 3, and week 6 of each treatment period.…”
Section: Chronic Selective Endothelin a Receptor Antagonism Reduces Smentioning
confidence: 99%